Natural Dye as an Alternative to Hematoxylin-Eosin Staining on Histological Preparations - Karlina, Ina; Pusparini, Nur Ainun Oktavia; Maharesi, Chesa Ekani; Saeed, Faisal; Retnoaji, Bambang; Saragih, Hendry; Septriani, Nur Indah; Rohmah, Zuliyati; Hadi, Susilo; Nuriliani, Ardaning (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2025)
Hematoxylin-eosin is widely utilized in the field of animal microtechniques. However, the need to develop alternative dyes from natural sources such as plants has gained attention. Several studies have shown that many plants contain secondary metabolites with the potential to be developed as natural dyes. Lonchocarpus cyanescens and Syzygium cumini are promising candidates as alternative dyes for hematoxylin, while Lawsonia inermis and Hibiscus sabdariffa have shown potential as substitute dyes for eosin. These plants contain various secondary metabolites, including anthocyanins, flavonoids, chlorophyll, betalains, alkaloids, saponins, tannins, carbohydrates, proteins, phenolics, terpenoids, quinones, coumarins, xanthones, and resins. L. cyanescens exhibits a strong binding affinity to cells and tissues, particularly testicular tissue. Dyes derived from Syzygium cumini have been shown to provide a good staining result for rat liver cells. In contrast, dyes from Lawsonia inermis can stain cytoplasmic components and muscle fibers. Additionally, the dye from Hibiscus sabdariffa is capable of staining various biological components, including sperm, nerve cells, and blood cells. The dye preparation process involved extraction from different plant organs, such as leaves, flowers, and fruit. These findings suggest that secondary metabolites from these four plants hold significant potential for development as natural dyes to replace hematoxylin-eosin in histological applications.